Fear of Cataract Surgery and Vision Loss: The Effects of Health Literacy and Patient Comprehension at an Academic Hospital-Based Eye Clinic - Hu S; Wey S; Yano RA; Kelly LD (Clinical Ophthalmology)
Samantha Hu,1 Stephanie Wey,1,2 Rainier Arthur Yano,1 Lisa Diane Kelly1,2 1University of Cincinnati College of Medicine, Cincinnati, OH, USA; 2University of Cincinnati Department of Ophthalmology, University of Cincinnati Medical Center, Cincinnati, OH, USACorrespondence: Samantha Hu, University of Cincinnati Department of Ophthalmology, 3130 highland Avenue, Cincinnati, OH, 45219, USA, Tel +1 720 879 3076, Fax +1 513 558 3108, Email hust@mail.uc.eduPurpose: This qualitative study assessed the relationship between health literacy and perceptions surrounding fear of cataract surgery and fear of vision loss in patients presenting to a Midwestern, urban, safety-net hospital-based clinic setting.Patients and Methods: Forty-two patients were recruited from the Hoxworth Eye Clinic at the University of Cincinnati Medical Center. The inclusion criteria were as follows: established patient at the clinic, age 50 or older, diagnosis of cataract by ICD-10 and/or physical exam, and no history of prior cataract surgery. Each patient completed a survey of demographic information and questions targeting their understanding and attitudes surrounding cataract pathology and treatment, and the Rapid Estimate of Adult Literacy in Medicine-Short Form (REALM-SF), a validated 7-item word recognition test assessing patient health literacy. Two-tailed t-tests assuming equal variances and chi-squared tests conducted in Excel were used in statistical analyses.Results: In our cohort (n = 42), there was no association between score on the REALM-SF and fear of cataract surgery (p = 0.87), but there was a significant association between fear of cataract surgery and belief that cataract surgery would improve vision (p = 0.03). Conversely, there was no significant association between fear of vision loss and belief that cataract surgery would improve vision (p = 0.92). The factors underlying these findings may be further clarified when attitudes surrounding cataract surgery and vision are categorized based upon best corrected visual acuity (BCVA). Patients with BCVA worse than 20/40 in only one eye fear cataract surgery more than patients with BCVA more than 20/40.Conclusion: In our patient population, neither health literacy nor understanding of cataract pathology was associated with fear of cataract surgery. However, given patients who feared cataract surgery were less likely to believe cataract surgery would improve vision, clarifying goals of surgery and addressing patient fears should be prioritized. Interestingly, this may be more important at earlier stages of non-visually significant cataracts for patients with good vision.Plain Language Summary: This study represents an effort to delineate what role, if any, health literacy plays in the uptake of cataract surgery, specifically aiming to understand underlying patient fears of cataract surgery and vision loss. In our context of a safety-net hospital for underinsured and uninsured patients, we hoped to describe the etiologies behind why patients might be reluctant to pursue cataract surgery, which is a leading cause of reversible blindness. We surveyed patients in our safety-net academic hospital on their perceptions surrounding cataract surgery and vision loss and assessed their health literacy through a validated word recognition test. The results suggest that neither health literacy nor a specific understanding of cataracts is associated with fear of cataract surgery. Rather, vision is a critical factor in perception; patients with better vision fear cataract surgery more. Therefore, addressing patient concerns earlier on in the cataract surgery process may better alleviate fears of the procedure itself and vision loss. Expanding our study to patients with English as their second language, countries outside the United States, and community hospitals would encompass more vulnerable populations and improve the generalizability of these findings.Keywords: vision loss, patient perceptions, safety-net eye clinic, cataract, health literacy